Equalisation of Children‘s Various Levels of Physical Activity Using Increased Physical Activity at School Among Ninth Graders - Lomsdal, Hege Hov; Lomsdal, Sondre Arntzen Arntzen; Lagestad, Pål (Frontiers in Public Health, 2022)
The purpose of this study was to examine whether 60 minutes of physical activity implemented during school hours, would have an impact on 15-year-olds' MVPA (moderate to vigorous physical activity) throughout the school day, and what effect it would have on low-, average-, and high- physically-active students. The intervention study included a sample of every 93 students in the ninth grade from a school in Trøndelag, Norway. Data on the students’ physical activity levels during schooltime were measured using accelerometers and analysed using the Actilife program. Statistical analyses were performed in SPSS, where the paired t-test and independent t-test were used to examine the research question. A significant higher change in MVPA was found in the intervention group compared to the control group, with an average increase of 25 minutes in MVPA in the pre-test to 42 minutes in post-test. Further analyses showed that the that both the low-active and the high-active had a significant increase in MVPA, taking the results of the control group into consideration. However, the low-active participants had the largest increase, with a 123% increase in MVPA during schooltime. The implication of the study is that PA interventions in school have the largest percentage effect among the low-active students in the study, which indicates that school-based interventions can be important in bridging social differences in MVPA among adolescents.